The Brand Scandal Spillover Effect at the Country Level: Evidence From Event-Related Potentials - Fan, Bonai; Li, Chen; Jin, Jia (Frontiers in Neuroscience, 2020)
The spillover effect of brand scandals commonly exists, and this effect will damage the image of the company, industry or even country in which the scandal occurred. Most previous studies on the brand scandal spillover effect have mainly focused on the corporate and industry levels. However, with the development of brand internalization and media technology, the spillover effect at the country level is becoming increasingly common. In the current study, we conducted an event-related potentials study to explore the spillover effect of brand scandals on the country level as well as its underlying neural basis. Specifically, we compared consumers’ attitudes toward countries of origin with different stereotypes during different types of brand scandals. When a competence scandal took place in a competence stereotype country, a larger P2 mean amplitude was elicited compared to a warmth stereotype country. When a morality scandal took place in a warmth stereotype country, a larger LPP mean amplitude was induced compared to a competence stereotype country. We explain the current results based on expectancy violations theory. When competence scandals take place in competence stereotype countries, there will be a greater degree of violation of expectations compared with that in warmth stereotype countries, which leads to a negative evaluation of the country of origin. When morality scandals take place in warmth stereotype countries, people had a stronger negative emotional arousal when morality scandals happened in the warmth stereotype country.